Dinamika Sistem Politik Indonesia dalam Penguatan Demokrasi Konstitusional di Era Transformasi Digital - Tia Irawan; Cahyono Cahyono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The development of Indonesia's political system in the post-reform era has demonstrated complex dynamics in line with social changes, economic developments, and advances in information technology. Political reforms initiated in 1998 have fundamentally transformed constitutional structures, democratic mechanisms, and the relationship between the state and society. At the same time, digital transformation has created new political spaces that influence citizens' participation in democratic processes. These developments present both opportunities and challenges for strengthening constitutional democracy in Indonesia. This article aims to analyze the dynamics of Indonesia's post-reform political system from the perspective of constitutional democracy in the era of digital transformation. The study employs a qualitative approach using library research methods. Data were collected from scholarly books, national and international journal articles, legislation, and other relevant official documents. Data analysis was conducted through content analysis involving data reduction, data presentation, and conclusion drawing. The findings reveal that Indonesia's political system has undergone significant progress through the strengthening of democratic institutions, direct elections, decentralization policies, and increasing political participation. Nevertheless, democratic quality continues to face several challenges, including money politics, political oligarchy, weak political party institutionalization, political polarization, and digital misinformation. Therefore, strengthening constitutional democracy requires continuous institutional reform, improvement of civic education, enhancement of digital literacy, and a strong commitment from all elements of society to uphold constitutionalism and the rule of law.